2021
DOI: 10.1177/21582440211029920
|View full text |Cite
|
Sign up to set email alerts
|

Rural–Urban Disparities in Access to Improved Sanitation in Indonesia: A Decomposition Approach

Abstract: One of the targets in the Sustainable Development Goals (SDGs), which is Target 6.2, aims to achieve access to adequate and equitable sanitation. The Government of Indonesia targets universal access to improved sanitation in 2019. However, almost two out of five households in Indonesia are without access to improved sanitation. Moreover, access to improved sanitation is lower in rural areas than that in urban areas. Studies examining the drivers of the disparity in Indonesia are also limited. Therefore, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
2
7
0
2
Order By: Relevance
“…Concerning rural-urban differences, utilization of improved sanitation was much higher in urban areas than in rural areas. These ndings are consistent with a study carried out in [10,12,20] and in other settings [34,35].…”
Section: Discussionsupporting
confidence: 93%
“…Concerning rural-urban differences, utilization of improved sanitation was much higher in urban areas than in rural areas. These ndings are consistent with a study carried out in [10,12,20] and in other settings [34,35].…”
Section: Discussionsupporting
confidence: 93%
“…This pattern was also found in extant studies [22,28,39]. More policies should be directed to accelerate universal access to improved sanitation facilities by considering the existing rural-urban gap [27]. In 2020, Statistics Indonesia reported a 13.34% gap in access to improved sanitation facilities between urban and rural areas in Indonesia [49].…”
Section: Discussionsupporting
confidence: 56%
“…Many Indonesian households do not possess access to improved drinking water sources, and of those, 42.30% rely on adult women as water carriers [25]. Rural-urban and regional disparities in access to water and sanitation still exist in Indonesia [26,27]. These poor conditions may contribute to the premature deaths of children.…”
Section: Introductionmentioning
confidence: 99%
“…More efforts are needed to ensure improvement on each determinant. For instance, a study on access to improved sanitation in Indonesia found that households living in rural areas were 11.35% less likely to have access to improved sanitation facilities than those residing in urban areas [25]. Efforts through more community empowerment may also be helpful.…”
Section: Discussionmentioning
confidence: 99%